HUKUM KHIYAR DALAM AKAD YANG MENGANDUNG PENIPUAN DALAM PERSPEKTIF HUKUM ISLAM - RINA PERMATA PUTRI (PREMISE LAW JURNAL, 2014)
ABSTRACT Sometimes the feeling of regret because of haste in making or cancelling a transaction will cause bad feeling, regret, or guilty feeling. This condition is sometimes used by those who have stronger position to make certain clauses in a contract which will be favorable for them. Besides that, giving wrong information about an object of a contract will cause the receiver of the information to be wrong in committing himself to a standard contract. Research on khiyar or optional right becomes very important for those who do transaction in a fraudulent contract since they have khiyar (Optional Right) to proceed or to cancel the contract. The research used judicial normative approach which analyzed written laws from literature materials or secondary data and legal references related to khiyar discussed in the research. The data were gathered by conducting library research with documentary study of primary and secondary data so that actual data or comparative data were obtained. A fraudulent contract which can harm one of the parties is a misleading action which intentionally deceives the ignorant partner, either orally or in action; there are also cunning tricks and lies orally and concealing information related to the object of a contract which is intentionally done to conceal the fact about the contract. Therefore, Islamic religion gives the right of akhyar to those who are harmed in the contract in the form of optional right to cancel or to proceed the contract. The parties in dispute because of the fraudulent contract can select reconciliation based on mutual agreement, but they can also select to file a claim to Court to cancel the contract. However, a contract which has fulfilled the requirement will be a valid contract although it is still sinful since it contains fraud in it. Keywords: Khiyar (Optional Right), Contract, Fraud